Escalation of antimicrobial resistance among MRSA part 1: focus on global spread. Issue 2 (1st February 2023) - Lynch, Joseph P.; Zhanel, George G.
ABSTRACT: Introduction: Staphylococcus aureus produce numerous virulence factors that influence tissue invasion, cytotoxicity, membrane damage, and intracellular persistence allowing them to be very common human pathogens. S. aureus isolates exhibit considerable diversity though specific genotypes have been associated with antimicrobial resistance (AMR) and toxin gene profiles. MRSA is an important pathogen causing both community-acquired (CA) and healthcare-acquired (HCA) infections. Importantly, over the past several decades, both HCA-MRSA and CA-MRSA have spread all over the globe. Even more concerning is that CA-MRSA clones have disseminated into hospitals and HCA-MRSA have entered the community. Factors that enhance spread of MRSA include: poor antimicrobial stewardship and inadequate infection control. The emergence and spread of multidrug resistant (MDR) MRSA has limited therapeutic options. Areas covered: The authors discuss the escalation of MRSA, both HCA-MRSA and CA-MRSA across the globe. A literature search of MRSA was performed via PubMed (up to September 2022), using the key words: antimicrobial resistance; β-lactams; community-associated MRSA; epidemiology; infection; multidrug resistance; Staphylococcus aureus . Expert opinion: Over the past several decades, MRSA has spread all over the globe. We encourage the judicious use of antimicrobials in accordance with antimicrobial stewardship programs along with infection control measures to minimize the spread of MRSA.